Experimenting with Machine Interpreting in the PL-EN Language Pair: Are We (Getting) Close to “Human-Like” Quality? - Korybski, Tomasz; Figiel, Wojciech; Tryuk, Małgorzata; Górnik, Michał (International Journal of Language, Translation and Intercultural Communication, 2026)
Recent claims from technology companies suggesting that machine interpreting (MI) technology is approaching human-level quality remain largely unsubstantiated by ecologically valid empirical evidence. To address this gap, an experiment was conducted in June 2025 at the Institute of Applied Linguistics, University of Warsaw, comparing human simultaneous interpreting and two leading MI service providers in the Polish–English language pair. The experimental design simulated a real-life conference setting: a tandem of EU-accredited interpreters and two MA-level interpreting students worked alongside the two MI systems during a live event comprising an introductory speech in Polish, a 40-minute lecture in English, and a bi-directional Q&A session. Eleven student observers provided subjective perception data through an online survey (non-controlled) while recordings and transcripts served as the basis for a detailed error analysis. This paper focuses on a presentation of the latter: to gain an understanding of interpretation accuracy across the four outputs we used a simplified error-based approach adapted from Barik’s typology of errors and later methods such as the NER and NTR (Romero-Fresco and Pöchhacker 2017) and their adaptations for interpreting research (Davitti and Sandrelli 2020, Korybski and Davitti 2024). A count of error instances in the transcripts reveals a clear quality sequence: accredited interpreters outperformed student interpreters, who in turn outperformed MI systems. As regards the weight of errors, machine-generated errors were more frequently of a major or meaning-distorting nature. This paper presents examples of common MI error types including misrecognitions propagated from automatic speech recognition, literal translations causing syntactic and stylistic distortions, redundant punctuation voicing, random language switches, and gender bias. Some errors clearly stem from a lack of contextual memory. In short, the overall speech-to-speech performance of the two MI systems lacked the flexibility, contextual awareness, and reformulation strategies characteristic of human interpreters. The findings suggest that, as of mid-2025 and given this experimental setup, MI in the PL-EN language pair remains far from human-like performance despite clear technological progress.